Rancangan Geometri Peledakan Untuk Mencapai Target Fragmentasi Ideal Berdasarkan Nilai Blastibility Index Pada Tamka PT. Allied Indo Coal Jaya Kota Sawahlunto - Syarif Hidayattullah; Bambang Heriyadi (Journals Mining Engineering : Bina Tambang, 2019)
Abstract. In blasting, the fragmentation of blasting results is influenced by the characteristics of rock masses, geological structures, groundwater, and others. Blastibility Index is a measurement of geological conditions and rock mass characteristics in blasting, in the measurement of blastibility index There are several parameters such as the rock mass description obtained RQD by 71,96% classified as a blocky rock, The joint mass description is classified as intermediate (space 0,1 m – 1 m), joint plane orientation (JPO) dip into face, specific grafity influence (25 x 2,68 - 50) obtained 17, hardness of 5,5. The blastibility index gained 51,25 with the 6,15 rock factor. In the lily chart is acquired geometry blasting design with a burden of 2,03m , spacing 2,85m, the dept of blast holes 6,09 m, PC 4,37 m, stemming 1,6 m, subdrilling 0,608 m, the explosives weight 17,994 kg/hole, powder factor 0,567 kg/m3. Actual fragmentation of the geometry design with the first lily chart  is embraced by the software Splitdesktop 2.0 obtained a fragmentation size of 50 cm at 6,31%. Design of the second blasting geometry burden 2,337 m, space 3,272m, the depth of the blast hole 7,011 m, PC  5,375 m, stemming  1,635 m, explosive weight 20,715kg/hole, powder factor 0,43 kg/m3.